Consideration of Docker based network deployment for a data center: GSDC in Korea - et.al, Jin Kim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For various operational reasons, this study presents a design and testbed environment for applying Docker-based system to a data center in Korea. We describe the design process of Docker based network. First, abstract structure is presented. Second, two conceptual routing models are provided. Third, the network plugin selection is stated. Then, we build Docker based system on a testbed environment as a pre-study for deployment to the entire system. There are plenty of factors to consider for the overall deployment. Representative factors include the routing method inside the server, the number of containers in a server, service arrangement by container, and response to equipment replacement. To evaluate those factors, various study should be performed with key system parameters. The proposed testbed environment can be utilized to obtain key system parameters. Applying Docker system to a data center can be remarkably efficient in terms of operations. The workload of operator will decrease, and scalability and flexibility will increase.